Winter Macro- and Microhabitat Use of Winter Roost Sites in Central Missouri - Eliodora Chamberlain; Ronald D. Drobney; Thomas V. Dailey (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) managers and biologists have expressed concern regarding the apparent decline of northern bobwhite populations throughout the Unites States. The decline has been attributed to habitat loss; however, the decline may be the result of multiple factors. Several studies concluded that reproduction was not a limiting factor, and recommended that investigations of winter habitat use at the microhabitat level are needed. In our study, we used data from 166 roost sites obtained from 194 radiomarked bobwhites to analyze winter macrohabitat use and microhabitat characteristics of roosts selected by bobwhites in central Missouri. At the macrohabitat level, bobwhites showed a preference for early successional vegetation (ESV), native warm-season grass (NWSG), and old (idle) fields. Most roost locations (5l.2%) were in old fields, in ESV (23%), and NWSG (l7%). For all 3 habitat types (old fields, ESV, NWSG), litter at the roost site was higher (P < 0.05) than the surrounding vegetation. In the 2 most preferred habitat types, visual obstruction reading (VOR) and maximum vegetation height were higher (P < 0.05) than the surrounding vegetation. In NWSG and old fields, litter depth was significantly higher (P < 0.05) than the surrounding vegetation. Habitat management of winter cover in central Missouri will benefit from the maintenance of dense ground litter (> 65%), tall vegetation (91 cm), VOR (29 cm), and litter depth about 1.5 cm in ESV, NWSG, and old fields.
Keywords: Colinus virginianus; macrohabitat; microhabitat; Missouri; northern bobwhite; winter habitat